2013
DOI: 10.1016/j.celrep.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Function of Archaeal DNA Replication Initiator Proteins

Abstract: SummaryChromosomes with multiple DNA replication origins are a hallmark of Eukaryotes and some Archaea. All eukaryal nuclear replication origins are defined by the origin recognition complex (ORC) that recruits the replicative helicase MCM(2-7) via Cdc6 and Cdt1. We find that the three origins in the single chromosome of the archaeon Sulfolobus islandicus are specified by distinct initiation factors. While two origins are dependent on archaeal homologs of eukaryal Orc1 and Cdc6, the third origin is instead rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
102
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(114 citation statements)
references
References 44 publications
(79 reference statements)
8
102
1
Order By: Relevance
“…Although this may simply reflect binding affinity in our in vitro assays conditions, it is conceivable that regulatory modifications to MCM and/or CG components in vivo could affect the strength of interaction we observe. Such a mode of regulation could provide a mechanism for the coordinate control of the three disparate origins present in the Sulfolobus chromosome (27).…”
Section: Discussionmentioning
confidence: 99%
“…Although this may simply reflect binding affinity in our in vitro assays conditions, it is conceivable that regulatory modifications to MCM and/or CG components in vivo could affect the strength of interaction we observe. Such a mode of regulation could provide a mechanism for the coordinate control of the three disparate origins present in the Sulfolobus chromosome (27).…”
Section: Discussionmentioning
confidence: 99%
“…These included replication fork-associated proteins such as the single-strand DNA binding protein (SSB); the replicative helicase MCM; the MCM-interacting factor Gins23; sliding clamp subunits PCNA1, 2, and 3; DNA ligase; replicative DNA polymerase polB1; and the clamp loader RFC. In addition, levels of WhiP, a homolog of the eukaryal pre-replicative complex protein Cdt1 that acts as the initiator protein that governs oriC3 (Robinson and Bell, 2007; Samson et al, 2013); the chromatin protein Alba (Bell et al, 2002); the candidate fork regression helicase Hel308; and the recombinase RadA (the RAD51/RecA ortholog) were unaltered in their levels following treatment with HU.…”
Section: Resultsmentioning
confidence: 99%
“…For oriC1 and oriC2 , this can be explained by the marked reduction of the cognate Orc1-1 and Orc1-3 initiator proteins (Robinson et al, 2004; Samson et al, 2013), and the consequent inability to detect Orc1-1 and Orc1-3 at origins by ChIP. However, levels of the WhIP protein, the initiator required for oriC3 , are not altered, and ChIP reveals that this protein remains associated with oriC3 even after treatment with 10 mM HU.…”
Section: Discussionmentioning
confidence: 99%
“…Studies using chromatin immunoprecipitation (ChIP) followed by analysis of the immunoprecipitated DNA on a wholegenome array chip (ChIP-chip studies) have revealed that the oriC is virtually the only site at which Pyrococcus abyssi Orc1/Cdc6 binds the genome (10). Recent work in Sulfolobus islandicus (11) has shown that two of its three origins are Orc1/Cdc6 dependent. Apart from origin recognition, Orc1/Cdc6 mediates the loading of the replicative helicase (MCM complex) onto DNA (12,13).…”
mentioning
confidence: 99%